Encephalocraniocutaneous Lipomatosis (Haberland Syndrome or Fishman Syndrome) - Garozzo, Maria Teresa; Attardo, Daniele; Smilari, Pierluigi; Greco, Filippo; Fiumara, Agata; Polizzi, Agata; Praticò, Andrea D.; Mazzurco, Marina; Pirrone, Concetta; Zanghì, Antonio; Schepis, Carmelo; Lacarrubba, Francesco; Micali, Giuseppe; Ruggieri, Martino (Journal of Pediatric Neurology, 2018)
Encephalocraniocutaneous lipomatosis is a sporadic, congenital neurocutaneous disorder characterized by the involvement of skin, central nervous system, and eye. A non-hereditary, autosomal mutation that may survive only in a mosaic state may be the cause of the clinical picture of the syndrome. Less than 80 patients have been so far reported and their clinical manifestations consisted of unilateral lipomatous hamartoma of the scalp or eyelid, epibulbar choristomas, and ipsilateral brain malformations. There is no clinical correlation between the severity of brain malformations and the clinical manifestations, and many patients with extremely extensive cerebral abnormalities are only minimal symptomatic. Seizures and mental retardation may also occur. The natural history is often favorable, without drug-resistant seizures and normal intelligence in most of the cases.
Keywords: encephalocraniocutaneous lipomatosis; Haberland syndrome; Fishman syndrome; epibulbar choristomas; brain malformations; seizures